2006
DOI: 10.1037/0090-5550.51.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of pain interference in multiple sclerosis.

Abstract: Objectives: To describe pain interference and explore its associations with several indexes of health and psychosocial functioning among veterans with multiple sclerosis (MS). Study Design: Cohort study linking computerized medical records and survey questionnaire. Participants: Four hundred fifty-one veterans with MS. Outcome Measures: Pain Effects Scale, Patient Health Questionnaire, Modified Social Support Survey, items from the Short Form Health Survey and the North American Research Consortium on MS Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Other than perceived social support and solicitude [9,67,74], all psychosocial predictors within regression models, usually in conjunction with other psychosocial factors, were significant, accounting for between 4 and 30% of the variance in pain severity and pain interference [9,53,57,66] (M. Glowacka, unpublished data, June, 2010: an unpublished dissertation). All studies (see Table 2) controlled for demographic and disease factors, whilst three controlled for pain severity when pain interference was the entered as the outcome variable [9,53] (M. Glowacka, unpublished data, June, 2010).…”
Section: Summary Of Regression Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other than perceived social support and solicitude [9,67,74], all psychosocial predictors within regression models, usually in conjunction with other psychosocial factors, were significant, accounting for between 4 and 30% of the variance in pain severity and pain interference [9,53,57,66] (M. Glowacka, unpublished data, June, 2010: an unpublished dissertation). All studies (see Table 2) controlled for demographic and disease factors, whilst three controlled for pain severity when pain interference was the entered as the outcome variable [9,53] (M. Glowacka, unpublished data, June, 2010).…”
Section: Summary Of Regression Findingsmentioning
confidence: 96%
“…In terms of pain interference, three good and one medium quality study indicated a medium to large positive relationship between depression and pain interference at the simple bivariate level (ranging from r = .28 to .60) [72][73][74] (M. Glowacka, unpublished data, June, 2010).…”
Section: Depressionmentioning
confidence: 99%
“…Determining the direction of the relationship have proved problematic, although there is some evidence among people with spinal cord injury to support the hypothesis than persisting pain is a driver of depression rather than the converse (Cairns, Adkins, & Scott, 1996;Putzke, Richards, Hicken, & DeVivo, 2002).The presence of depression at one time point has been reported to be a risk factor for pain at a later time point among those with multiple sclerosis and spinal cord injury (Buchanan, Wang, Tai-Seale, & Ju, 2003;Putzke, et al, 2002). Depression is associated with pain-related interference in a number of physically disabling conditions, including amputation, multiple sclerosis and spinal cord injury (Kratz, et al, 2010;Norrbrink Budh, et al, 2005;Norrbrink Budh & Osteraker, 2007;Osborne, et al, 2006;Turner, et al, 2002). There is evidence of a similar moderating effect of depression upon the relationship between pain and disability among those with spinal cord injury as is seen in other chronic pain populations (Borsbo, Peolsson, & Gerdle, 2009), and a similar but less clear interaction between these variables in those with traumatic brain injury (Hoffman, et al, 2007).…”
Section: Mood and Mental Healthmentioning
confidence: 99%
“…In a study conducted among veterans with MS, increased fatigue, poor general health, and greater depression symptom severity were significantly associated with higher levels of pain. Therefore, pain should be treated aggressively to minimize functional impairment [51]. Also, preventing pain due to extended seating in wheeled mobility devices should be addressed.…”
Section: Psychosocial Factors and Mobility Assistive Technology Use Pmentioning
confidence: 99%
“…In cases in which only family members are available to decide on an AT device, their decision could have detrimental effects on the psychosocial wellbeing of persons with MS if they feel that they do not have control over or input into the kind of equipment obtained [50]. Persons with MS and their family should discuss and agree on the risks and benefits of the AT to be used to maintain a supportive environment with good adaptation to the new device [51]. An open relationship between persons with MS, their family members, and rehabilitation professionals involved in prescribing an AT device will result in better outcomes [34,50].…”
Section: Psychosocial Factors and Mobility Assistive Technology Use Pmentioning
confidence: 99%